Superphanes with CpCo-stabilized cyclopentadienone units: synthesis and properties - Roers, Rolf; Rominger, Frank; Nuber, Bernhard; Gleiter, Rolf (Organometallics, 2000)
The cyclic alkynes 5-cyclononynone (23) and 5-cyclodecynone (24) were dimerized by heating with CpCo(CO)2 to form the tricyclic CpCo-stabilized cyclopentadienone derivatives 25 and 26, respectively. These diketones were transformed to the tricyclic diynes 30, 31, and 33, via the corresponding bis(selenadiazoles). Whereas the diynes 30 and 31 did not yield the desired bis(cyclopentadienono)phanes, we were successful with 33. Heating of 33 in the presence of CpCo(CO)2 at 150 °C yielded the intramolecular cycloaddition product 34 and the mixed superphane 35. Irradiation of 33 in the presence of CpCo(CO)2 at 5 °C yielded the 2-fold CpCo-capped bis(cyclopentadieno)superphane 44. The key compounds of this reaction sequence, 26a, 31, 33, 34, and 44, have been characterized by X-ray structural analysis.